Acoustic and magnetic properties of magnetic fluids - SKUMIEL, A.; HORNOWSKI, T.; JÓZEFCZAK, A. (Archives of Acoustics, 1999)
The influence of magnetic field on the acoustic and magnetic properties of magnetic liquids is discussed. By fitting the curve of Taketomi’s theory to the experimental data of the anisotropy of ultrasonic attenuation, the values of quantities describing the structure of magnetic liquid have been determined. Moreover, the dependence of magnetic susceptibility on frequency has been measured. It shows that two processes of magnetization, which are based on the mechanisms proposed by Brown and Néel, contribute to the magnetization of the EMG-605 magnetic liquid.